PROBLEMS USING INNOVATIVE TECHNOLOGIES IN TEACHING ENGINEERING (American Journal of Pedagogical and Educational Research, 2022)
This article's main objective is to demonstrate how cutting-edge technologies may be used to teach effectively. The advantage of using this article method is the capacity to efficiently gain communication proficiency. A communicative strategy focuses on improving international contact skills and communication skills, which are the cornerstones of how the Internet operates. The Internet is an international, multinational, cross-cultural society whose livelihoods depend on electronic communication between millions of simultaneously across the globe. This conversation is the largest in terms of size and number of participants in a conversation that has ever taken place.